2020
DOI: 10.3889/oamjms.2020.5021
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Impact on Physicians’ Decision-making: Digoxin Toxicity in View of Combination of Hydroxychloroquine and Azithromycin: A Case Report

Abstract: BACKGROUND: Since the WHO declaration of COVID-19 being a global pandemic, the population in general and health-care providers, in particular, became under extraordinary pressure that remarkably impacts their decisions at multiple levels as all of us should make decisions quickly while being uncertain in many times. CASE REPORT: We are reporting a 64-year-old lady with a medical history of atrial fibrillation and mitral regurgitation that treated with digoxin and warfarin therapy, she was suspected to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Thus, COVID-19 patients using digoxin for CHF are at increased risk of digoxin toxicity and serum digoxin levels should be closely monitored. 2 Furthermore, atrial fibirllation and flutter were observed in 16% of hospitalised patients with COVID-19 and 60% of arrhythmias were reported as new onset. 3 However, due to the high mortality risk, atrial fibrillation and flutter should be treated, even with the risk of drug toxicity.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, COVID-19 patients using digoxin for CHF are at increased risk of digoxin toxicity and serum digoxin levels should be closely monitored. 2 Furthermore, atrial fibirllation and flutter were observed in 16% of hospitalised patients with COVID-19 and 60% of arrhythmias were reported as new onset. 3 However, due to the high mortality risk, atrial fibrillation and flutter should be treated, even with the risk of drug toxicity.…”
mentioning
confidence: 99%
“…1 Increased intracellular calcium due to inhibition of Na-K transporter is the primary pathway of digoxin toxicity. 2 Factors such as renal function, age, lean body weight, cytokine levels and concomitant medications should be considered carefully during digoxin treatment to minimise toxicity. 1 Digoxin toxicity may cause various electrocardiographic changes.…”
mentioning
confidence: 99%
See 2 more Smart Citations